INCIDENCE AND ETIOLOGY OF HYPOSPADIAS (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
Hypospadias can be defined as incomplete virilization of the genital tubercle that causes an insufficient development of the tissues forming the ventral aspect of the penis. Three associated anomalies are classically found in the hypospadiac penis: an ectopic opening of the urethral meatus located at any place between the glans and the base of the penis, a ventral curvature of the penis (chordee), and a hooded foreskin with a marked excess of skin on the dorsum of the penis and a lack of skin on the ventrum.